Therapeutic Drugs and Devices for Tackling Ocular Hypertension and Glaucoma, and Need for Neuroprotection and Cytoprotective Therapies - Sharif, Najam A. (Frontiers in Pharmacology, 2021)
Damage to the optic nerve and the death of associated retinal ganglion cells (RGCs) by elevated intraocular pressure (IOP), also known as glaucoma, is responsible for visual impairment and blindness in millions of people worldwide. The ocular hypertension (OHT) and the deleterious mechanical forces it exerts at the back of the eye, at the level of the optic nerve head/optic disc and lamina cribosa, is the only modifiable risk factor associated with glaucoma that can be treated. The elevated IOP occurs due to the inability of accumulated aqueous humor (AQH) to egress from the anterior chamber of the eye due to occlusion of the major outflow pathway, the trabecular meshwork (TM) and Schlemm’s canal (SC). Several different classes of pharmaceutical agents, surgical techniques and implantable devices have been developed to lower and control IOP. First-line drugs to promote AQH outflow via the uveoscleral outflow pathway include FP-receptor prostaglandin (PG) agonists (e.g. latanoprost, travoprost and tafluprost) and a novel non-PG EP2-receptor agonist (omidenepag isopropyl, Eybelis®). TM/SC outflow enhancing drugs are also effective ocular hypotensive agents (e.g. rho kinase inhibitors like ripasudil and netarsudil; and latanoprostene bunod, a conjugate of a nitric oxide donor and latanoprost). One of the most effective anterior chamber AQH microshunt devices is the Preserflo® microshunt which can lower IOP down to 10-13 mmHg. Other IOP-lowering drugs and devices on the horizon will be also discussed. Additionally, since elevated IOP is only one of many risk factors for development of glaucomatous optic neuropathy, a treatise of the role of inflammatory neurodegeneration of the optic nerve and retinal ganglion cells and appropriate neuroprotective strategies to mitigate this disease will also be reviewed and discussed.